Minimizing Paper Machine Downtime at PT DAP Using the Reliability-Centered Maintenance (RCM) Approach - Yogi Setyo Widodo; Moch Anshori (Faculty of Engineering, Universitas Serambi Mekkah, 2026)
PT. DAP is a manufacturing company in the pulp and paper industry that faces frequent machine breakdowns and downtime, which adversely affect the achievement of production targets. This study aims to develop a maintenance strategy to minimize downtime on the PM1 paper machine using the Reliability-Centered Maintenance (RCM) approach. The results indicate that the critical components of the Palm Guide Roll system are the Air Bellow, Pneumatic Air Cylinder, and Paddle Blade. The recommended optimal replacement intervals are 24 days for the Air Bellow, 53 days for the Pneumatic Air Cylinder, and 54 days for the Paddle Blade. The proposed maintenance strategy applies a Time-Directed (TD) maintenance policy to the Air Bellow and Pneumatic Air Cylinder, and a Condition-Directed (CD) maintenance policy to the Paddle Blade. The proposed maintenance strategy is expected to reduce the Total Minimum Downtime (TMD) of the critical components by 4.74% and decrease component replacement costs by IDR 20,444,146.34 (4%) on the paper machine.